(untitled) (Journal of Dhaka National Medical College & Hospital, 2022)
Background: Cervical cancer is the second most common cancer among women in Bangladesh. Cervical cancer is a preventable disease as it has a long precancerous stage. Routine and effective screening detects the disease at its precancerous stage and can reduce the incidence of cervical cancer by almost 80%. Visual Inspection of the cervix with 5% acetic acid allows for inspection of the ace to-white area (VIA Positive). Objective: To evaluate cervical preconcert screening in tertiary level hospital of Bangladesh. Methods: This cross-sectional study was conducted in the gynecology Department of Sir Salimullah Medical College and Mitford Hospital, Dhaka from January 2018 to December 2019. Women who came for cervical cancer screening by VIA were included in this study. A total of 1023 women were included in this study. VIA-positive cases were evaluated in colposcopy clinics where the ’see and treat’ policy applied. The specimen was sent for a Histopathology examination. Results: Among 1023 women, 92 were VIA positive (8.99%). Colposcopy test among VIA positive women, 21 (22.82%) were normal, 39 (42.39%) were CIN-1 and 29 (31.52%) were CIN-2 & CIN-3, 3 were unsatisfactory (3.26%). In CIN-1, cryotherapy was given to 21 patients. LEEP was done in 18 patients of CIN-1, all 29 patients of CIN-2 & CIN-3. The histopathology report showed chronic cervicitis with squamous metaplasia in 15 patients, CIN-1 in 20 patients, CIN-2 in 8 patients, CIN-3 in 3 patients and invasive cancer in 1 patient. Conclusion: VIA is safe and feasible in our country. The hopeful news is that women are eager to gather knowledge about carcinoma cervix. We will achieve the goal of reducing the mortality rates associated with cervical cancer. J. Dhaka National Med. Coll. Hos. 2022; 28 (02): 35-38